HUBUNGAN RIWAYAT PENYAKIT DENGAN STATUS GIZI : STUDI CROSS SECTIONAL - Nur, Zuhra Tun; Suryana, Suryana; Yunianto, Andi Eka (JURNAL RISET GIZI, 2021)
Background: Children who often suffered from diseases will affect their nutritional status.Purpose: To determine the risk factors of disease history with nutritional status among stunted children under-five in Pidie Jaya Regency.Methods: A descriptive-analytic study with a cross-sectional design. Total sample were 34 children. Weaning initiation patterns and disease history were obtained through interviews with questionnaire. The nutritional status among children under five were measured by anthropometric. Data were analyzed using chi-square test.Results: Children's disease history in the last three months were correlated with the nutritional status on the HAZ index (P-value = <0.015 (<0.05) with OR = 6.0. There was no correlation betweeen disease history with the nutritional status by WAZ and WHZ index (P-value> 0.05).Conclusion: The history of the disease in the last 3 months has a significant relationship with HAZ of children under five.